MODEL INTEGRASI PROGRAM BISNIS DALAM MISI ORGANISASI UNTUK PERUMUSAN STRATEGI BERKELANJUTAN PADA PERUSAHAAN ALAT BERAT - Yuliyana, Andrean Prayuda; Aziz, Iqbal Abdul; Kodiri, Kodiri; Supratikta, Hadi (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The heavy equipment industry is under increasing pressure to transform in response to regulatory requirements, market volatility, and the growing urgency of sustainability. Despite this, many companies continue to experience fragmentation across their Environmental, Social, and Governance (ESG), Corporate Social Responsibility (CSR), and Net-Zero initiatives, which are frequently implemented in isolation and lack alignment with core business strategy. This study aims to develop a conceptual model that integrates these business programs into the organizational mission to support the formulation of a cohesive and sustainable strategy. The research adopts a qualitative model-development approach, combining a Systematic Literature Review (SLR) to identify key variables with a multiple case study analysis of four leading heavy equipment companies: PT United Tractors Tbk, Caterpillar Inc., Komatsu Ltd., and PT Hexindo Adiperkasa Tbk. The results propose the Mission–Program–Strategy (MPS) Integration Model. This model positions the organizational mission (the why) as an active strategic filter that aligns and integrates business programs (the what), ultimately enabling the formulation of a coherent and actionable sustainable strategy (the how). The case studies reveal that leading firms such as PT United Tractors through its “10 Sustainability Aspirations” and Caterpillar through its strong emphasis on the circular economy have intuitively applied the underlying logic of this model. The findings offer important managerial implications by providing a practical framework for industry leaders to bridge the gap between sustainability strategy formulation and implementation, while transforming the organizational mission from a passive statement into a functional strategic instrument.